2019
DOI: 10.21203/rs.2.13760/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasound Assessment of Tensile Stress in Carotid Arteries of Healthy Human Subjects with Varying Age

Abstract: Background: Arterial remodeling is thought to reflect the adaptation of the vessel wall to mechanical and hemodynamic stimuli and contributes to the progression of cardiovascular and cerebrovascular diseases. Tensile stress (TS) is one of the mechanical properties of the artery wall. The purpose of this study was to investigate the tensile stress change (TS) of carotid artery with varying viscoelasticity in healthy subjects within two groups of different ages. Methods: Forty-five subjects were recruited and r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…On the other hand, API may re ect the stiffness of muscular arteries and is more susceptible to the response degree of cellular mechanoreceptors. The fact that both blood pressure and pulse are based on cellular mechanoreceptors causes the changes in vascular structure and function, which lead to changes in vascular viscoelasticity and residual stress [31,32]. This is consistent with the ndings of our study that blood pressure and pulse affect API independently.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, API may re ect the stiffness of muscular arteries and is more susceptible to the response degree of cellular mechanoreceptors. The fact that both blood pressure and pulse are based on cellular mechanoreceptors causes the changes in vascular structure and function, which lead to changes in vascular viscoelasticity and residual stress [31,32]. This is consistent with the ndings of our study that blood pressure and pulse affect API independently.…”
Section: Discussionsupporting
confidence: 92%
“…Mechanical stretching can cause structural alteration of the arterial wall, including hyperplasia and hypertrophy of vascular smooth muscles, leading to arterial remodeling. Carotid tensile stress is related to its elasticity, 23 and Claudio et al 24 found that Carotid endothelial shear stress reduction is an independent predictor of atherosclerosis. In addition, in a previous study, 25 increased TG levels and decreased HDL‐C levels were related to arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%